Composite alternatives in group decision support - Rudolf Vetschera (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1992)
Decision theoretic models of group decision processes usually assume a given set of alternatives, about which the decision has to take place. In realistic group decision situations, however, alternatives are often not specified a priori, but are created during the group process from different components introduced by the group members. This paper develops methods for systematically creating such composite alternatives, taking also into account the necessity to keep both the computational effort and the cognitive load to group members within reasonable limits.
Keywords: 330